Conversor inversor integrado três estados buck-boost para geração distribuída, com operação conectada ou ilhada - Guzmán Lascano, Cindy Paola [UNESP] (2015)
The current motivation of growing need for new alternative energy sources, as well as by improvements in technologies for energy conversion systems, this study proposes the use of the single-phase tri-states Buck-Boost integrated converter for the use of energy from solar photovoltaic systems. Photovoltaic systems provide DC voltages and, on the other hand, the large majority of machines or domestic use loads require alternating voltage with RMS values of 127 V or 220 V in Brazil. This points out to the need to study of DC-AC converter structures, known as inverters. Due to the limitation that the alternating voltage supplied by the inverters are dependent on the maximum value of the input voltage, the inclusion of an elevator stage in the general system is necessary, before providing power to the load, thus resulting in a reduction in the performance by the number of components, increased weight and volume. In this dissertation, the studied inverter performs, in a single structure, the functions of the elevator stage or reducer stage, also performs the continues in alternating voltage conversion function, ensuring reduced levels of harmonic distortion in the current injected to the main grid and the output voltage in islanding mode, with an increase performance in the output voltage, and that should provide power to loads connected in both modes islanding or grid connected. In the presented converter, the switching system of three states has improved the behavior of dynamic characteristics due to the addition of the third estate, simplifying the control by eliminating the zero present in the right half-plane of the transfer function of Buck-Boost inverter, controlled in voltage mode. For the development of control strategies is adopted the mathematical model for instantaneous average values. The modeling of the structure is made by the mean values method in the state spaces. Additionally, is carried out a review and assessment of some ...